2017
DOI: 10.1371/journal.pntd.0005877
|View full text |Cite
|
Sign up to set email alerts
|

Post-kala-azar dermal leishmaniasis in the Indian subcontinent: A threat to the South-East Asia Region Kala-azar Elimination Programme.

Abstract: BackgroundThe South-East Asia Region Kala-azar Elimination Programme (KAEP) is expected to enter the consolidation phase in 2017, which focuses on case detection, vector control, and identifying potential sources of infection. Post-kala-azar dermal leishmaniasis (PKDL) is thought to play a role in the recurrence of visceral leishmaniasis (VL)/kala-azar outbreaks, and control of PKDL is among the priorities of the KAEP.Methodology and principal findingWe reviewed the literature with regard to PKDL in Asia and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
137
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 63 publications
1
137
0
4
Order By: Relevance
“…1 L. naiffi infection in humans is limited to the states of Amazonas, Acre, Pará, Rondônia and Mato Grosso, 16 with no complications having been reported until our study revealed the first case of CL caused by L. naiffi in Amapá. L. infantum is phylogenetically close to Leishmania donovani, the agent that causes VL and post-kala-azar dermal leishmaniasis in the Old World (Europe); 17 occurrence of cutaneous lesions caused by L. infantum in immunocompetent individuals is uncommon in the Americas, especially in Brazil. 14,18 L. infantum has been isolated in the skin of Africans with CL, producing a lesion histologically distinct from that caused by L. major.…”
Section: Discussionmentioning
confidence: 99%
“…1 L. naiffi infection in humans is limited to the states of Amazonas, Acre, Pará, Rondônia and Mato Grosso, 16 with no complications having been reported until our study revealed the first case of CL caused by L. naiffi in Amapá. L. infantum is phylogenetically close to Leishmania donovani, the agent that causes VL and post-kala-azar dermal leishmaniasis in the Old World (Europe); 17 occurrence of cutaneous lesions caused by L. infantum in immunocompetent individuals is uncommon in the Americas, especially in Brazil. 14,18 L. infantum has been isolated in the skin of Africans with CL, producing a lesion histologically distinct from that caused by L. major.…”
Section: Discussionmentioning
confidence: 99%
“…One recurrent observation is that patients treated for VL in health services are predominantly male [2,3]. This is not limited to the Indian subcontinent but was observed across different geographical locations, over different leishmanial species and disease spectra, including cutaneous forms of leishmaniasis [2,[4][5][6]. Two hypotheses have been formulated to explain this difference between both sexes, stressing either social differences between men and women (i.e., gender differences, relating to the specific behavior, activities, and roles of men and women in society) or biological differences (i.e., sex differences) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Miltefosine is currently being used as anti-parasitic oral drug for treating PKDL which can easily accessible and safe to use [11,12]. Previous study also demonstrated the treatment with miltefosine for 12 weeks (50 mg twice per day) has a cure rate of 93% (per protocol [PP] analysis) [13]. In Indian subcontinent, PKDL cases are treated according to national guidelines with miltefosine for 12 weeks with miltefosine.…”
Section: Discussionmentioning
confidence: 99%